2017
DOI: 10.1158/1535-7163.mct-17-0211
|View full text |Cite
|
Sign up to set email alerts
|

Potency-matched Dual Cytokine–Antibody Fusion Proteins for Cancer Therapy

Abstract: A novel biopharmaceutical, consisting of the F8 mAb (specific to a splice isoform of fibronectin) simultaneously fused to both TNF and IL2, was found to react with the majority of solid tumors and hematologic malignancies in mouse and man, but not with healthy adult tissues. The product selectively localized to neoplastic lesions , as evidenced by quantitative biodistribution studies using radioiodinated protein preparations. When the potency of the cytokine payloads was matched by a single-point mutation, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 48 publications
(85 reference statements)
1
73
0
Order By: Relevance
“…Hypotension, leukopenia, thrombocytopenia, fever, headache, nausea and hepatopathy represent the most common side effects detected in Phase II studies with recombinant TNF, while most serious toxicities include respiratory failure and coagulopathies [32]. Our group has previously demonstrated that the generation of antibody-TNF fusion proteins capable to selectively accumulate to tumors after systemic administration represents a valuable strategy to improve therapeutic window and efficacy of TNF [15][16][17]. L19-TNF is an antibody-fusion protein for the targeting of the alternatively-spliced EDB domain of fibronectin [33], that shows potent antitumor activity in preclinical models of cancer [9,34,35] and is now being investigated in clinical trials [13,18,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypotension, leukopenia, thrombocytopenia, fever, headache, nausea and hepatopathy represent the most common side effects detected in Phase II studies with recombinant TNF, while most serious toxicities include respiratory failure and coagulopathies [32]. Our group has previously demonstrated that the generation of antibody-TNF fusion proteins capable to selectively accumulate to tumors after systemic administration represents a valuable strategy to improve therapeutic window and efficacy of TNF [15][16][17]. L19-TNF is an antibody-fusion protein for the targeting of the alternatively-spliced EDB domain of fibronectin [33], that shows potent antitumor activity in preclinical models of cancer [9,34,35] and is now being investigated in clinical trials [13,18,36].…”
Section: Discussionmentioning
confidence: 99%
“…While therapeutic activity can be dramatically improved by the selective delivery of cytokines to tumors via antibodies [19][20][21], toxicity profile is often similar to the one of unmodified cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, a progressive decrease in the cumulative %ID/g value in the tumor mass was observed [ Figure 2D]. The targeted delivery of TNF to the tumor blood vessels may cause a rapid and selective shutdown of the vasculature, leading to hemorrhagic necrosis [25,36,37,61]. The conversion of a tumor mass into a necrotic scab within the first few hours is likely to prevent product accumulation for subsequent injections.…”
Section: Figure 1e Depicts a Biodistribution Rationale For Using Intrmentioning
confidence: 98%
“…TNF is a homo-trimeric pro-inflammatory cytokine, mainly produced by macrophages, NK and T cells [10,11]. TNF is involved in inflammatory processes and as indicated by its name, it may display a potent anticancer activity against some malignancies, by promoting hemorrhagic necrosis and by inducing direct apoptosis of tumor cells [12][13][14][15][16][17]. Moreover, TNF may activate the immune system as a result of the increased inflammation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%